Enhancing Arabic Language Skills in Elementary Students Through TBLT: A Qualitative Literature Synthesis - Herdiani, Salvia; Devira Saharani; Syifa Bilqis Tsaniya; Rachmatul Azizah; Lala Adawiyah (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This qualitative descriptive study investigates the implementation, task forms, and impact of Task-Based Language Teaching (TBLT) on Arabic language proficiency in elementary school students. Despite Arabic's importance in Islamic- based primary education, traditional methods often lead to passive learning and limited communicative competence. TBLT, emphasizing meaningful tasks and real- world language use, offers a student-centered alternative. Employing library research with content analysis and source triangulation of reputable journals (last 5-10 years), the study examines TBLT application stages (pre-task, task cycle, post- task), varied task types (role-play, descriptive tasks, retelling, simple projects), and its effects. Results indicate TBLT significantly enhances speaking (maharah al- kalam), listening (maharah al-istima'), vocabulary (al-mufradat), and grammar (qawaid), alongside crucial affective and socio-emotional aspects like motivation, confidence, and collaboration. While implementation faces challenges such as limited task variation and technology integration, TBLT fosters an interactive, meaningful learning environment, shifting focus from teacher-centered instruction to active student engagement. This research contributes to localized TBLT theory, advocating for adaptable, context-appropriate models and offering practical guidance for teachers and curriculum developers to improve elementary Arabic language education